Benchmarking of business incubators final report. - Centre for Strategy & Evaluation Services.; European Commission. Directorate-General for Enterprise and Industry (Sevenoaks CSES, 2002)
On cover p.: European Commission Enterprise Directorate- General. Draft version (2001) includes the Company questionnaire.
Keywords: Business creation; UE/CE action programs; UE/CE member states